Music and (re-)translating unity and reconciliation in post-genocide Rwanda - Barz, Gregory (Acta Academica: Critical views on society, culture and politics, 2012)
This article focuses on the ability of a historically important musical instrument in the East African country of Rwanda, the inanga, to contribute to the (re-)translation of issues related to unity and reconciliation efforts after the genocide of 1994. By concentrating on the transmission of tradition from Kirusu Thomas to Sophie Nzayisenga, from father to daughter, I underscore the significant changes in cultural contexts for historical and contemporary inanga performance while also positioning the instrument within the dominant cultural metaphors of ‘blockage’ and ‘flow’. Throughout the article, I draw on inanga song texts to demonstrate the role of the inanga as cultural translator.